Effect of calcination on the sintering behaviour of hydroxyapatite - The Y.C.; Tan C.Y.; Ramesh S.; Purbolaksono J.; Tan Y.M.; Chandran H.; Teng W.D.; Yap B.K. (Institute of Chemical Technology, 2023)
In this study, a wet chemically produced hydroxyapatite (HA) powder was subjected to calcination at 700, 800, 900 and 1000°C. Subsequently, the sintering behaviour of these calcined powders was studied at various temperatures, ranging from 1050 to 1350°C. XRD results revealed that calcination has no effect on the phase stability of hydroxyapatite. However, the XRD peaks showed that the crystallinity of the powder increased with increasing calcination temperature. The specific surface area of powder reduced drastically from 60.74 m2·g-1 to 9.45 m2·g-1 with increasing calcination temperature. The SEM micrographs of calcined powder showed the coarsening of powder particles as the calcination temperature was increased. In terms of sinterability, the uncalcined HA powder sintered at 1150°C was found to possess the optimum properties with the following values being recorded: ? 99 % relative density, Vickers hardness of 7.23 GPa and fracture toughness of 1.12 MPa·m1/2. The present research indicated that calcination of the HA powder prior to sintering has a negligible effect on the sintering behaviour of the HA compacts and that calcination at 1000°C was found to be unfavourable to the properties of sintered HA.